A new species of Eleutherodactylus (Amphibia: Anura: Brachycephalidae) from the western flank of the Cordillera Oriental of Colombia - Mueses-Cisneros, Jonh Jairo (Zootaxa, 2006)
A new species of the Eleutherodactylus conspicillatus group is named from the western flank of the Cordillera Oriental of Colombia in the departamento de Santander. The species is similar to E. savagei Pyburn and Lynch and E. carranguerorum Lynch, although it is also similar to E. douglasi Lynch of the E. galdi group with which it is sympatric. Eleutherodactylus. padrecarlosi n. sp. differs from the previous species in external morphology, size and osteology. This new species, with E. ixalus Lynch and E. w-nigrum (Boettger) are at the moment the only three species of the E. conspicillatus group those occur on the western flank of the Cordillera Oriental of Colombia.